Cabozantinib llus nivolumab in adult patients with advanced or metastatic renal cell carcinoma: a retrospective, non-interventional study in a real-world cohort/GUARDIANS project - Hilser, Thomas Klaus Joseph Wilhelm; Darr, Christopher; Niegisch, Günter; Schnabel, Marco Julius; Foller, Susan; Häuser, Lorine; Zschäbitz, Stefanie; Lewerich, Jonas; Ivanyi, Philipp; Schlack, Katrin; Paffenholz, Pia Valerie; Daetwyler, Eveline; et al. (Cancers, 2024)
Introduction: Combinations of immune-checkpoint inhibitors (ICIs) are the standard of care (SOC) for treatment-naive metastatic renal cell carcinoma (mRCC) patients. In this multicenter study, we evaluated the RW safety and efficacy of cabozantinib plus nivolumab in mRCC patients. Methods: Data were retrospectively collected from twelve cancer centers in Germany, Switzerland, and Austria. Patients with advanced or mRCC were eligible. The investigator-based objective response rate (ORR) and progression free survival (PFS) were calculated from the start of the treatment to progression or death. Descriptive statistics and Kaplan-Meier (KM) plots were utilized where appropriate. Results: In total, 96 eligible patients (66.6% male) with a median age of 66.0 years were included. The most common histology was clear-cell RCC (ccRCC) in 63.4% (n = 61). A prior nephrectomy was performed in 60.4% (n = 58). ECOG 0-1 was 68.8% (n = 66). A partial response was documented in 43.8% of patients (n = 42), a stable disease in 32.3% (n = 31), and a progressive disease in 8.3% (n = 8) as the best overall response. Response data were not evaluable in 13.5% (n = 13). The median follow-up time was 12.7 months (95% CI, 10.0-15.3). The PFS rate at 6 months was 89.8% in the overall population (86.8% for ccRCC; 90.0% for non-ccRCC). Adverse events (AEs) were reported in 82.3% (n = 79) for all grades and 41.7% (n = 40) for grades 3-5. Elevated liver enzymes (34.4%), diarrhea (31.3%), and hand-foot syndrome (29.2%) were the three most frequent AEs of any grade and causality. Discussion/Conclusions: In this real-world cohort of mRCC patients, the application of cabozantinib plus nivolumab was shown to be safe and feasible. Our data support the use of cabozantinib plus nivolumab as a first-line standard therapy in mRCC patients. Major limitations were the retrospective data capture and short follow-up time of our study.